2008
DOI: 10.1088/1126-6708/2008/06/014
|View full text |Cite
|
Sign up to set email alerts
|

Metastable domains of the landscape

Abstract: We argue that the vast majority of flux vacua with small cosmological constant are unstable to rapid decay to a big crunch. Exceptions are states with large compactification volume and supersymmetric and approximately supersymmetric states. Neither weak string coupling, warping, or the existence of very light particles are, by themselves, enough to render states reasonably metastable. We speculate, as well, about states which might be cosmological attractors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…35 once the vacuum energies are known. This can be compared with the analysis of [20,21], where such thin-wall transitions were considered. In reality, there will most likely be a spectrum between thin-and thickwall solutions, determined by the hierarchy of scales between the barrier height and the vacuum energy splitting.…”
Section: Discussionmentioning
confidence: 99%
“…35 once the vacuum energies are known. This can be compared with the analysis of [20,21], where such thin-wall transitions were considered. In reality, there will most likely be a spectrum between thin-and thickwall solutions, determined by the hierarchy of scales between the barrier height and the vacuum energy splitting.…”
Section: Discussionmentioning
confidence: 99%
“…Their work showed that a sharp accumulation of vacua generally occurs near the conifold locus in moduli space. Dine et al [8] used scaling arguments to conclude that vacua in the string landscape with small cosmological constant become unstable when fluxes are large relative to their compactification volume. Chen et al [19] and Marsh et al [20] showed that increasing the number of moduli fields suppresses exponentially the chance that a randomly chosen critical point will be a minima, with the suppression growing for vacua with high energy.…”
mentioning
confidence: 99%
“…On the other hand, Dine and collaborators [28] have given cogent arguments that the small c.c. and hierarchically small weak interaction scale do imply low SUSY breaking scale in the Landscape.…”
Section: Environmental Selection Of Parametersmentioning
confidence: 99%
“…The authors of [28] examined non-perturbative instabilities of locally stable dS stationary points. They argue that even though individual semi-classical tunneling probabilities are small, the vast number of possible final states in the Landscape would render many of these points unstable rather than meta-stable.…”
Section: Environmental Selection Of Parametersmentioning
confidence: 99%
See 1 more Smart Citation